Effects of agricultural pond eutrophication on survival and health status of Scinax nasicus tadpoles - Peltzer, Paola (2008)
To test the hypothesis that eutrophication ponds modulate some aspects of the health responses and survival of anuran tadpoles, we conducted field experiments using Scinax nasicus as sentinel organism to evaluate the quality of two ponds filled with agricultural runoff in a dominant agricultural landscape of Mid-Western Entre Ríos Province (Argentina). The survival, growth and development rates, erythrocytes nuclei aberrations, parasite infection, and brain cholinesterase activity were monitored after seven days of exposure. Water samples from the ponds were also analyzed for physico-chemical variables and levels of pesticide residues. Residues of organochlorine pesticides and nutrients were higher in the agricultural ponds with respect to those from the control pond. We suggest that the interactions among washed-off nutrients and pesticides from agriculture and environmental factors account for deleterious effects on S.nasicus survival, growth and development rate, thereby compromising their health status. These effects can lead, in turn, to an increase in tadpole vulnerability to opportunistic parasites, erythrocytes nuclei aberrations or hemolysis.